Mean amplitudes of vibration of the BrO3F2- anion - Baran, Enrique José (2006)
The mean amplitudes of vibration of the recently characterized BrO3F2 - anion, containing Br(VII), were calculated from its spectroscopic and structural data in the temperature range between 0 and 1000 K. The results are compared with those of related species and the bond peculiarities of the new anion are also briefly discussed.